Anti-leishmanial evaluation of C2-aryl quinolines: Mechanistic insight on bioenergetics and sterol biosynthetic pathway of Leishmania braziliensis (2013)
A series of diverse simple C2-aryl quinolines was synthesized de novo via a straightforward synthesis based on the acid-catalyzed multicomponent imino Diels–Alder reactions. Seven selected quinolines were evaluated at different stages of Leishmania braziliensis parasite. Among them, the 6-ethyl-2-phenylquinoline 5f was able to inhibit the growth of promastigotes of this parasite without affecting the mammalian cells viability and decreasing the number of intracellular L. braziliensis amastigotes on BMDM macrophages. The mechanism of action studied for the selected compound consisted in: (1) alteration of parasite bioenergetics, by disrupting mitochondrial electrochemical potential and alkalinisation of acidocalcisomes, and (2) inhibition of ergosterol biosynthetic pathway in promastigote forms. These results validate the efficiency of quinoline molecules as leishmanicide compounds.